2017
DOI: 10.1007/s10157-017-1399-4
|View full text |Cite
|
Sign up to set email alerts
|

Renal infarct volume and renal function decline in acute and chronic phases

Abstract: The volume of the infarction may be a factor in the degree of renal function decline in ARI. Therefore, assessment of infarct volume in ARI is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
11
0
2
Order By: Relevance
“…Similarly, another study observed that although acute kidney injury was present in 40.7% of the study patients, long-term renal outcome was relatively good [10]. The volume of the infarction has been suggested to be a factor in the degree of renal function decline in acute renal infarction [11].…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, another study observed that although acute kidney injury was present in 40.7% of the study patients, long-term renal outcome was relatively good [10]. The volume of the infarction has been suggested to be a factor in the degree of renal function decline in acute renal infarction [11].…”
Section: Discussionmentioning
confidence: 96%
“…Renal dysfunction with high morbidity can also be seen after RI. Renal dysfunction is associated with the size of the infarction area [12,13]. Patients with renal dysfunction before RI, bilateral cases and unilateral global infarctions often present with impaired renal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha asociado al pico del valor de la LDH con el volumen del infarto y con la disminución del filtrado glomerular en la fase aguda del infarto pero no en la fase crónica (46) . Esto haría a la LDH como la opción más apropiada dentro de los marcadores serológicos para despistar el diagnostico en vista a solicitar una tomografía con contraste o si se tuviera una tomografía no concluyente como un elemento para orientar el diagnostico.…”
Section: Discussionunclassified
“…Previamente se ha reportado que el desarrollo de injuria renal tanto aguda como progresión a la enfermedad renal crónica se asocia a mayor edad, diabetes mellitus (32) , y mayor volumen del infarto (46) . Y se ha relacionado la ocurrencia de injuria renal con el grado de proteinuria y la presencia de hematuria microscópica, niveles más altos de AST, ALT, LDH (4) y PCR (32) .…”
Section: Discussionunclassified